A Contextual Approach to Political Theory - Carens, Joseph H. 1945- (2004)
This article explores the advantages of using a range of actual cases in doing political theory. This sort of approach clarifies what is at stake in alternative theoretical formulations, draws attention to the wisdom that may be embedded in existing practices, and encourages theorists to confront challenges they might otherwise overlook and to think through the implications of their accounts more fully.
Keywords: Walzer; reflective disequilibrium; Practice; Kymlicka; Culture; contextual political theory; Cases